2015
DOI: 10.5944/openpraxis.7.4.228
|View full text |Cite
|
Sign up to set email alerts
|

Teaching strategies to promote immediacy in online graduate courses

Abstract: The present study is the result of the research question: How do teachers promote immediacy through interaction with their students in online graduate courses? Research was carried out at Tecnológico de Monterrey, a Mexican private university that offers online courses. The research methodology employed a qualitative approach of virtual ethnography, which entails non-participative observation and interviews with head professors and teaching assistants with the purpose of exploring the manner in which teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…It was evident that e-learning strategies established a supportive rapport that successfully qualifies for quality indicators for the online education system. The results aligned with the study of Rahim 2021 (16) , and Fahara et al, (17) who indicated similar qualities such as time spent in the learning atmosphere, days posted (Course content) on the portal, the number of feedback made to students within a discussion, and timeliness of responses to students' questions and grading of assignments considered as a measure of quality. Students revealed verbal immediacy by calling the students by name, using humor, and encouraging students' input and discussion.…”
Section: Discussionsupporting
confidence: 86%
“…It was evident that e-learning strategies established a supportive rapport that successfully qualifies for quality indicators for the online education system. The results aligned with the study of Rahim 2021 (16) , and Fahara et al, (17) who indicated similar qualities such as time spent in the learning atmosphere, days posted (Course content) on the portal, the number of feedback made to students within a discussion, and timeliness of responses to students' questions and grading of assignments considered as a measure of quality. Students revealed verbal immediacy by calling the students by name, using humor, and encouraging students' input and discussion.…”
Section: Discussionsupporting
confidence: 86%
“…Again, the argument can be made that feelings of closeness are relevant to rapport building. Research generally reflects this assumption and implies that immediacy has needed to be a teaching behavior utilized by educators due to students appreciating the nonverbal behaviors highlighted by immediacy (Fahara & Castro, 2015). However, the findings of this study contradict a viewpoint that is widely agreed upon in the field of education.…”
Section: Theoretical Implicationsmentioning
confidence: 44%
“…Further, this finding has the potential of shaping future research on teacher behaviors and preservice teacher education. Immediacy has often been described as feelings of closeness, which one could assume has been relevant to rapport building (Fahara & Castro, 2015). Again, the argument can be made that feelings of closeness are relevant to rapport building.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Theoretical frameworks such as the community of inquiry (Garrison et al, 2010) were used to design learning experiences (teaching presence) and communication opportunities to establish trust and shared purpose (social presence) within the LMS (Cooper & Scriven, 2017). Teachers can develop immediacy (psychological closeness) and the learning community through collaborative problem-based or projectbased learning supported with discussion boards (Fahara & Castro, 2015), in which students explained concepts and case studies, shared knowledge and resources, sought help, gave feedback and monitored group effort (Ngai et al, 2019). An LMS and VoiceThread software enabled digital storytelling incorporating peer feedback to encourage reflection, critical thinking and empathy development (Price et al, 2015).…”
Section: Lmssmentioning
confidence: 99%
“…(c) Self-regulated learning was promoted by familiarising students with technologies, clearly communicating expectations, facilitating peer interaction and feedback (Fleischmann, 2019;McCarthy, 2015), and encouraging reflection (Pinya & Rossello, 2016). (d) Climate, emotional engagement and social presence can be promoted through group learning activities with technologies to facilitate collaboration and communication (Fahara & Castro, 2015). Learning designs and technologies can help widen participation through supporting disadvantaged groups (Kreniske et al, 2019, Wilks et al, 2017 and promoting accessibility of learning resources and activities (Stokes, 2017), and provide global perspectives and connections to promote intercultural understanding (Guariento et al, 2016).…”
Section: Implications For Practicementioning
confidence: 99%